Wyłączenie odpowiedzialności karnej za błąd medyczny w czasie pandemii COVID-19 - Tomczak, Maria (Kortowski Przegląd Prawniczy, 2021)
The COVID-19 pandemic has caused a rapid growth in medical malpractice perpetrated by totality of medical staff. New regulations were mandated by legislator so as to introduce rules restricting responsibility of a medic in particular and necessary cases. Art. 24 of newly constituted Act issued on October, 28 2020 modified some effective acts in accordance with countering crisis situation associated with Coronavirus outbreak. Legislator stated a normative solution that cancelled criminality of actions taken during pandemic. Acts mentioned in the incoming law refers to art. 155, art. 156 § 2, art. 157 § 3, art. 160 § 3 of Polish Penal Code. The main and essential prerogative of amendment is the attitude of suspect who is to perform in peculiar circumstances and proof of precaution required in an exceptional instance. The article points out the outlook on regulations established recently that consists of consequences of medical malpractice during pandemic and legal responsibilities as its repercussion. Undoubtedly, the rule is the privilege for doctors who needs to face the unknown situation.